PENETEPAN METODE AKTIVA TETAP BERWUJUD PADA PT. BPR ALSABA PRIMA - Reza Saleh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
Accountancy is one medium to running stabilize condition as company need.Accountancy is get basically active process stabilizes starting to get active release or erase. Research problem will discuss is “How is treating active accountancy and financial report of CV Bahana Karya Gresik. Research kindsof this thesis is using descriptive with qualitative approach calls givingdescription about accountancy application to stabilize active that companyget with financial report. The writer is using collecting data method withobservation, interview and documentation. According to this research resultmention that CV. Bahana Karya is doing confession, measurement,decreasing, stopping and presenting to active suitable to PSAK No 16.Key words: created active and financial report.